Use of electronic vaping products and mental health among adolescent high school students in the United States: The moderating effect of sex. (March 2022) - Baiden, Philip; Szlyk, Hannah S.; Cavazos-Rehg, Patricia; Onyeaka, Henry K.; Peoples, JaNiene E.; Kasson, Erin
Abstract: Although studies have investigated the association between conventional tobacco smoking and mental health outcomes among adolescents in the United States, few studies have examined the association between electronic vaping products (EVPs) and mental health among adolescents. This study aimed to investigate the cross-sectional association between EVPs use, symptoms of depression, and suicidal behaviors among adolescents. Data were pooled from the 2017 and 2019 Youth Risk Behavior Survey. An analytic sample of 14, 285 adolescents (50.3% female) was analyzed using binary logistic regression. The outcome variables investigated were symptoms of depression, suicidal ideation, suicide plan, and suicide attempts, and the main explanatory variable was EVPs use. Of the 14, 285 adolescents, 22.2%, 19.2%, and 58.8% were current, former and never users of EVPs, respectively. Controlling for other factors, current users of EVPs were significantly more likely to report having symptoms of depression ( AOR = 1.82, 95% CI = 1.58–2.09), having suicidal ideation ( AOR = 1.55, 95% CI = 1.30–1.86), making a suicide plan ( AOR = 1.62, 95% CI = 1.34–1.97), or attempting suicide ( AOR = 1.75, 95% CI = 1.41–2.18) when compared to never users of EVPs. Gender moderated the association between EVPs use, symptoms of depression, suicidal ideation, and suicide plan. Racial minority identity, sexual minority identity, sexual violence victimization, victim of school and cyberbullying, alcohol use, and cigarette smoking were all significantly associated with depression and suicidal behaviors. Study findings support the association between EVPs use and adolescent mental health. Future studies that employ longitudinal designs may offer more insight into the mechanisms underlying this association. Highlights: About one in five adolescents were current users of electronic vaping products (EVPs). Current and former users of EVPs were more likely to report depression and suicidal behaviors than never users. Sex moderated the association between EVP use, symptoms of depression, suicidal ideation, and suicide plan.